Servant Leadership and Personality on Performance through Organizational Culture: Evidence from Private Universities in Bekasi City - Saing, Bungaran; Moeins, Anoesyirwan; Muharam, Hari (International Journal of Social and Management Studies, 2024)
This study aims to explore the influence of servant leadership and personality on lecturer performance in higher education, considering organizational culture as a mediating variable. The research tool used is a cross-sectional quantitative study with a questionnaire (survey) of 250 respondents for all lecturers of Private Universities in Bekasi City using a Structural Equation Model with a mediation fit approach to prove the role of the context. This study provides empirical evidence that lecturer performance is influenced by servant leadership and personality with organizational culture as a mediating fit. The results of this analysis include positive guidance, particularly on the importance of the leader's role in empowering and encouraging lecturers through active engagement with them, and the existence of organizational principles that positively enhance college performance.